An application for vehicle rental service advertising using geofence with content-based filtering (ReadyVehicle) / Muhammad Rizzuan Ariff Subano … [et al.] - Subano, Muhammad Rizzuan Ariff; Abdul Rahid @ Abdul Rashid, Nurul Najwa; Ab Malek, Ezzad; Pahruradzi, Salman; Baddru’l-Sham, Ezrren Natasha (Faculty of Business and Management, 2023)
Vehicle rentals have been a popular practice for many years. Some individuals prefer renting vehicles for their flexibility and affordability, especially in areas with limited public transportation options. However, finding rental services on the internet can be a cumbersome task. Therefore, this project aims to create a mobile application for advertising vehicle rental services in Jasin and Merlimau, Melaka, using geofencing and content-based filtering. The solution used will allow rental providers to create advertisements in specific areas, notifying potential renters as they enter these designated areas. This project has been tested using functionality testing to evaluate the mobile application functionality.